Perancangan Standar Operasional Prosedur (SOP) Pembelajaran MBKM Berbasis Analisis SERVQUAL dan QFD - Aulawi, Hilmi; Sukonoya, Muhammad Fajar (Institut Teknologi Garut, 2025)
The implementation of the Merdeka Belajar-Kampus Merdeka (MBKM) program faces operational challenges that have resulted in a teaching material achievement rate of only 93.4 percent, which is below the institutional target. This study aims to design Standard Operating Procedures (SOPs) to improve the quality of MBKM learning services through the integration of the SERVQUAL and QFD methods. Primary data were collected through questionnaires from 90 students and 10 lecturers. The SERVQUAL analysis results showed a negative gap in all service attributes, indicating that perceptions did not meet expectations, with one of the largest gaps found in the aspect of lecturer competency assurance (-0.70). Importance-Performance Analysis (IPA) identified responsiveness as the top priority for improvement. Based on this priority, this study produced a validated SOP design for students and lecturers. This SOP is expected to serve as an operational guideline for standardizing and continuously improving the quality of MBKM learning services.